Does the establishment of universal health coverage drive the foundation of postgraduate education for primary care physicians? (Medical Journal of Indonesia, 2017)
Background: Studying the formation of postgraduate training in primary care within countries which has attained Universal Health Coverage (UHC) is important to support the development of similar training in low-and middle-income countries aiming to achieve UHC by 2030. This review aims to describe the state of postgraduate training for primary care physicians in UHC-attaining countries.Methods: A literature review of published literature and official documents from the websites of regional and global health/primary care organizations or societies such as World Health Organization (WHO), World Organization of Family Doctors (WONCA), European Forum for Primary Care, European Union of General Practitioners (GP)/Family Physicians (FP), European Academy of Teachers in GP/Family Medicine (FM), as well as the websites of GP/FP organizations in each of the respective countries. The list of UHC attained countries were identified through WHO and International Labor Organization databases.Results: A total number of 72 UHC-attained countries were identified. Postgraduate education for primary care physicians exists in 62 countries (86%). Explicit statements that establish primary care postgraduate training were corresponded with the policy on UHC is found in 11 countries (18%). The naming of the program varies, general practice and family medicine were the commonest. In 33 countries (53%), physicians are required to undertake training to practice in primary level. The program duration ranged from 2â6 years with 3 years for the majority.Conclusion: Although UHC is not the principal driving force for the establishment of postgraduate training for primary care physicians in many countries, most UHC-attaining countries make substantial endeavor to ensure its formation as a part of their health care reform to improve national health.